Determinación del perfil hemático en llamas adultas en la asociación Intiñán provincia de Chimborazo - Chango Pilaluisa, María José (2016)
Currently, the Llamas production occurs primarily in geographical areas located at altitudes of 3800 m, leading to a hypobaric hypoxia as a stressor on the morphological and physiological adaptations thereof. The goal research "Determination of hepatic profile in adult llamas at Intiman Chimborazo province association”. It produces a diagnostic evaluation, nutrition assistance and medications, in order to establish a laboratoriesreferencesource around the country. The research work were applied in 32 animals, 16 are females and 16 males llamas. One erythrocyte count, hemoglobin, hematocrit, mean corpuscular volume, hemoglobin concentration, mean corpuscular hemoglobin and mean corpuscular cell morphology sheet: automated quantification method which was used showed the blood sampling. The results were in hematologic intervals adults of both sexes llamas are within the referencerange impedance electronic machine….